“Nuclear Winter” Hypothesis Research and Responsibilities in Nuclear Policy - A. S. Ginzburg; N. A. Samoylovskaya (Международная аналитика, 2024)
In the 1980s, one of the fundamental topics of scientific debate was the discussion of the global consequences of nuclear war. At that time, the hypothesis of “nuclear winter” emerged, in which scientists attempted to analyse the theoretical possibility of a sharp cooling of the Earth after mass fires, and to find natural analogues of a potential climatic catastrophe. In the following decades, the “nuclear winter” hypothesis went through various stages of criticism and reassessment. In the early 2000s, studies of the problem became regional in nature, focusing mainly on the possible consequences of local nuclear conflicts. In this article, the authors analyse the stages of development of research on the “nuclear winter” hypothesis, focusing on the Russian and American approaches, and conclude that the body of work produced by American and Soviet scientists in 1983–1985 represents the first attempts by the scientific community to conceptualise the problem of responsible nuclear policy.